2022
DOI: 10.1177/23333936211042616
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Complementary Medicine During Childbearing Years: A Multi-Country Study of Women From the Middle East

Abstract: The prevalence of self-prescribed complementary medicine (CM) use is an area of concern across the Middle East. We conducted a descriptive qualitative study to describe women’s use of CM during their childbearing years in Egypt, Jordan, Saudi Arabia and Iran. The study conducted using face to face audio-recorded interviews with 70 participants. Our findings showed that women used several herbal plants to ease pain and discomfort during menstruation and/or during pregnancy and in postpartum care. Acupuncture, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Despite that, 23.70% firmly believed that traditional herbs can treat PCOS. This can be explained by the cultural belief in using traditional herbs to treat illnesses in the Middle East, especially gynecological problems such as hormonal imbalances and infertility [ 39 ]. Another study reported a prevalence of up to 82.3% use of herbal medicine during pregnancy in the same region [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, 23.70% firmly believed that traditional herbs can treat PCOS. This can be explained by the cultural belief in using traditional herbs to treat illnesses in the Middle East, especially gynecological problems such as hormonal imbalances and infertility [ 39 ]. Another study reported a prevalence of up to 82.3% use of herbal medicine during pregnancy in the same region [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the cultural belief in using traditional herbs to treat illnesses in the Middle East, especially gynecological problems such as hormonal imbalances and infertility. [40] Another study reported a prevalence of up to 82.3% use of herbal medicine during pregnancy in the same region. [41] Likewise, 31.90% and 11.80% were confident that good hygiene and vaccines can prevent PCOS, respectively.…”
Section: Figure F How Frequently Was Each Treatment Methods Chosen?mentioning
confidence: 97%
“…The consumption of date palm fruit (DPF), commonly named dates, is a typical behavior among women from the Middle East during the final month of gestation [ 20 ]. In different traditional medicines, DPF is also highly recommended to be consumed by parturients and breastfeeding mothers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%